2000
DOI: 10.1021/ac991099z
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Low Molecular Weight Anions through a Nafion Ionomer Membrane:  Application to Kraft Cooking Liquors

Abstract: The permeation of low molecular weight anions from liquors having high ionic strengths through a Nafion 811 membrane in Na+ form has been studied. The penetration of solutes through the membrane was monitored using UV-visible spectrometry. A relation between penetration and ionic size has been established. The influence of the presence of other ions on the permeation has also been investigated. The results show that the membrane has great potential as part of a selective interface in applications where the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…It is normally expected to be permselective and to completely reject cations due to their electrical charge, which is identical to the one of the fixed sites. Actually, as it has been observed for Nafion [14], a slight permeation of cations can occur, especially when the ionic strength of the solutions is high, according to the ™Donnan potential∫ theory.…”
Section: Potential Response Of Tosflex-coated Gc Electrodes Towards Amentioning
confidence: 72%
“…It is normally expected to be permselective and to completely reject cations due to their electrical charge, which is identical to the one of the fixed sites. Actually, as it has been observed for Nafion [14], a slight permeation of cations can occur, especially when the ionic strength of the solutions is high, according to the ™Donnan potential∫ theory.…”
Section: Potential Response Of Tosflex-coated Gc Electrodes Towards Amentioning
confidence: 72%
“…However, Danielsson and Yang [5] showed that molecules with molecular weights higher than that of AHQs could diffuse through the membrane. Therefore, it was hypothesized that the electronic structure of the AHQs could have an impact.…”
Section: Hydroquinone Behaviormentioning
confidence: 99%
“…Later data show that there is an inverse relationship between the penetration efficiency of an anionic compound in a tubular Nafion membrane and the molecular weight of that compound [5]. Here, penetration efficiency is defined as the ratio of the concentration in the acceptor stream to the concentration in the donor stream.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations